2022
DOI: 10.37077/25200860.2022.35.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Halopriming and Hormopriming in Regulating the Vegetative Growth and Seed Quality of Vicia faba L.

Abstract: High seed quality and growth performance is farmer’s and agricultural enterprise’s demand. However, increasing population increases food demand and due to global warming and limited natural resources, more attention has been paid to implementing different effective strategies. Halopriming and hormopriming have shown improvement in different growth and developmental stages in plants and under adverse environmental conditions. Therefore, this study was aimed to study the interaction impact of halopriming and hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In this study, germination and seedling growth were increased with hydro-and hormopriming applications. Similarly, Alom et al (2016) reported the same results in wheat, three bean and two sorghum cultivars, and Moori and Ahmadi-Lahijani (2020) thyme, Kka et al (2022) faba bean crops. Seedling growth parameters (SL, RL, SFW, RFW) Salinity reduces plant growth through osmotic and toxic effects.…”
Section: Discussion Discussion Discussionmentioning
confidence: 59%
“…In this study, germination and seedling growth were increased with hydro-and hormopriming applications. Similarly, Alom et al (2016) reported the same results in wheat, three bean and two sorghum cultivars, and Moori and Ahmadi-Lahijani (2020) thyme, Kka et al (2022) faba bean crops. Seedling growth parameters (SL, RL, SFW, RFW) Salinity reduces plant growth through osmotic and toxic effects.…”
Section: Discussion Discussion Discussionmentioning
confidence: 59%